Learners Perspective On The Teaching Techniques Apllied By The Native And Non-Native Teachers In English Department Of Muhammadiyah University Of Surakarta In 2014/2015 Academic Year - Rachmanzah, Gillang Nur, Aryati Prasetyarini , S. Pd, M. Pd, Drs. Djoko Srijono, M. Hum (2017)
This study is aimed at describing the techniques used by the native and non-native lecturers in teaching speaking skill in the department of English education at the University of Muhammadiyah Surakarta. Methods of data collection in this study are observation, interview and documentation. The results of this study present some learner's perspective about classroom techniques applied by lecturers native and non-natively and learners perspective in the department of English Language University of Muhammadiyah Surakarta. Techniques used by non-native lecturer are role-play and discussion. Role-play technique used by the teacher is to allow students immediately apply content as they are put in the role of a decision maker who must make a decision regarding a policy, resource allocation, or some other outcome. Discussion technique used by the lecturer is to improve the students speaking ability. Techniques used by native lecturer are role-play and games. From the results found concluded that the technique used by non-native lecturer is effective for students. Students think that the techniques used by native and non-native teachers are good for improving speaking skills. But there are some problems with the techniques used by the native lecturer they are the students are still limited in grammar, vocab and pronunciation. Keywords: Teachers Teaching Techniques of non-indigenous, native Teachers Teaching techniques, and Learners persective.